Perspective student about role education citizenship in building a sense of nationalism at UNIWARA - Laili, Innayatul; Lestari, Sely Ayu; Damayanti, Ayu Maya; Siswantoro, M. Irwawan; Daryono, Daryono (Jurnal Ilmu Pendidikan dan Humaniora, 2026)
Amidst the challenges of globalization that erode national identity, Civic Education in higher education becomes an important instrument to foster students' sense of nationalism. This study aims to determine the perspectives of students at Universitas PGRI Wiranegara (Uniwara) regarding the role of Civic Education in building an attitude of love for the homeland. Using a qualitative approach, data were collected through in-depth interviews with several students from various faculties. The findings show that students view Civic Education as an effective means to understand the values of Pancasila, the history of the nation's struggle, and civic responsibility, which strengthens the sense of nationalism. However, they were criticized the monotonous teaching methods and the lack of relevance of the material to current issues, such as tolerance and diversity. This study implies the need for Civic Education curriculum reform with an interactive approach, such as group discussions and the use of digital media, to increase its relevance and impact in forming contextual nationalism. These findings contribute to the development of educational strategies that are responsive to the needs of the younger generation in the global era, especially at Uniwara, and strengthen the commitment of higher education in maintaining national identity